Double emulsion-pretreated microwell culture for the in vitro production of multicellular spheroids and their in situ analysis - Fuyang Qu; Shirui Zhao; Guangyao Cheng; Habibur Rahman; Qinru Xiao; Renee Wan Yi Chan; Yi-Ping Ho (Microsystems & Nanoengineering, 2021)
Abstract Multicellular spheroids have served as a promising preclinical model for drug efficacy testing and disease modeling. Many microfluidic technologies, including those based on water–oil–water double emulsions, have been introduced for the production of spheroids. However, sustained culture and the in situ characterization of the generated spheroids are currently unavailable for the double emulsion-based spheroid model. This study presents a streamlined workflow, termed the double emulsion-pretreated microwell culture (DEPMiC), incorporating the features of (1) effective initiation of uniform-sized multicellular spheroids by the pretreatment of double emulsions produced by microfluidics without the requirement of biomaterial scaffolds; (2) sustained maintenance and culture of the produced spheroids with facile removal of the oil confinement; and (3) in situ characterization of individual spheroids localized in microwells by a built-in analytical station. Characterized by microscopic observations and Raman spectroscopy, the DEPMiC cultivated spheroids accumulated elevated lipid ordering on the apical membrane, similar to that observed in their Matrigel counterparts. Made possible by the proposed technological advancement, this study subsequently examined the drug responses of these in vitro-generated multicellular spheroids. The developed DEPMiC platform is expected to generate health benefits in personalized cancer treatment by offering a pre-animal tool to dissect heterogeneity from individual tumor spheroids.